2000
DOI: 10.1002/(sici)1097-4636(20000605)50:3<353::aid-jbm9>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of human osteoblastic cells on stoichiometric hydroxyapatite and type A carbonate apatite: Role of surface energy

Abstract: Abstract:To determine the role of physicochemical characteristics of the surface of dense ceramics on osteoconduction, we studied the proliferation and differentiation of human trabecular (HT) osteoblastic cells, extracellular collagenous matrix production, and biologic apatite formation on stoichiometric hydroxyapatite (HA) and type A carbonate apatite (CA). The surface physicochemical characteristics (composition, roughness) of HA and CA carefully were determined by Fourier-transformed infrared, X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(129 citation statements)
references
References 0 publications
9
117
0
3
Order By: Relevance
“…Recently it has been demonstrated in the literature that these effects can be expressed in the cell at the level of genomic regulation, thus contributing to very fundamental changes in cellular physiology, ultimately resulting in unknown adjustments to cellular proliferation, motility and, in some cases, phenotype [17][18][19][20][21][22][23]. In this work we have demonstrated that measurements of cellular proliferation and viability on coated spectroscopic substrates can be correlated with spectral changes induced by adjustments to cell physiology when cultured on the different coatings.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Recently it has been demonstrated in the literature that these effects can be expressed in the cell at the level of genomic regulation, thus contributing to very fundamental changes in cellular physiology, ultimately resulting in unknown adjustments to cellular proliferation, motility and, in some cases, phenotype [17][18][19][20][21][22][23]. In this work we have demonstrated that measurements of cellular proliferation and viability on coated spectroscopic substrates can be correlated with spectral changes induced by adjustments to cell physiology when cultured on the different coatings.…”
Section: Resultsmentioning
confidence: 66%
“…This ultimately results in increasing proliferation and motility, which is also dependent on the charge distribution presented by the ECM coating molecule to the adhering cell [18][19][20][21][22][23]25]. Ultimately the reaction of the cell to such influences are complex, being the cumulative effect of the increased or decreased regulation of a number of stimulatory pathways in the cell, with the end physiological change in any given cell being dependent on the cell and substrate ECM [50,51].…”
Section: Fluorescence/absorbance Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the improved wettability of the HA surfaces resulted from other factors. The modification of surface wettability on HA was reportedly achieved by A-type carbonate apatite, corresponding to the location of carbonate ions on monovalent anionic OH -sites 3 and by fluoridated HA, incorporating fluorine in HA 4 . However, the improvement of HA surface wettability by polarization did not affect structural transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The former subject, surface characteristics, including the topography, constituent elements, functional group, and wettability of biomaterials affect osteoblast attachment and adhesion 2 . The surface characteristics were reportedly affected by surface roughness, surface crystallinity 2 , the constituent elements at the surface, and the incorporation of ions such as carbonate or fluorine 3,4 . In addition, electron-induced surface energy modifications such as photoluminescence and surface photovoltage spectroscopy were also effective in the improvement of the surface characteristics 5 .…”
Section: Introductionmentioning
confidence: 99%